BIALL at 50: the Noughties. (June 2019) - Fogden, Fiona
Abstract : It is apt to start this review about the 2000s by mentioning 'a project called UKILELI…it aims to create a database of UK full-text legislation and case transcripts; available via the web. More critically it aims to be free.' It was later renamed to the more easily pronounced BAILII. BIALL had voted to support the project with a donation and to encourage law libraries to do the same.